Gender differences in geriatric depressive symptoms in urban China: the role of ADL and sensory and communication abilities - Guo, Ling; Fang, Mingwang; Wang, Lingying; Liu, Li; He, Chunxia; Zhou, Xiumei; Lu, Yi; Hu, Xiuying (Frontiers in Psychiatry, 2024)
Objectives ADL and Sensory and Communication Abilities are important indicators of the quality of life of the elderly which are significant determinants of health, particularly in developing countries. The present cross-sectional study investigated effect of ADL and Sensory and Communication Abilities on depressive symptoms, as well as the the role of gender in these effects. Design This is a cross-sectional study. Setting A nationally representative cross-sectional survey among the Chinese population aged 60 years and over. Participants A total of 163296 females and 148724 males aged 65 and over in 2019 in urban China. Outcome measures Prevalence, risk factors and gender differences in geriatric depressive symptoms among urban elderly. Results Approximately 95.69% of the participants had depressive symptoms according to the CESD-10, with no statistically significant gender difference of 52.15% in females and 47.85% in males. Logistic regression findings suggest that geriatric depressive symptoms are significantly associated with the lack of eldercare (OR=2.427, female; OR=1.426, male), living alone(OR= 1.430, female; OR= 1.179, male), ADL dysfunction (OR=1.528, female; OR=1.246, male), and impaired sensory and communication ability (OR=1.338, female; OR=1.185, male) among both female and male participants. Remarkably, geriatric depressive symptoms are only significantly associated with age (≥75, OR = 1.327), marital status (unmarried, OR=1.598), the number of children (no children, OR=2.271), and the living arrangement (living alone, OR= 1.430) among female participants. Conclusion Significant gender differences in these associations were found for living alone, ADL dysfunction and impaired sensory and communication ability. Moreover, the study emphasized that the gender difference exists in terms of geriatric depression in urban China. Females are more likely to experience depressive than males with the same circumstances.